MODELLING STRESS-STRAIN RELATIONS OF SAND - SIDDIQUEE, MOHAMMED S.A.; ABE, FUMIHIRO; PARK, CHOONSIK; TATSUOKA, FUMIO; SAKAMOTO, MAKOTO (SOILS AND FOUNDATIONS, 1993)
A modelling method for highly nonlinear shear stress-strain relations in plane strain compression of a fine sand, Toyoura Sand, which has been used extensively in a large number of model tests by many researchers, is attempted taking into account the effects of many major factors; (1) void ratio, (2) confining pressure σ3, (3) the initial and maximum shear modulus Gmax as observed at strains less than about 0.001%, (4) anisotropic strength and deformation characteristics, (5) strain softening associated with strain localization into a shear band, and (6) the stress ratio during consolidation. The model is based on a modified hyperbolic equation. By the model proposed, a relation from very small strain (0.0001%) to the residual conditions through smooth transition from pre-peak to post-peak relations can be generated for a given condition. A generated stress-strain relation has a tangent modulus which is continuous at the peak strength state between the pre-peak and post-peak parts.